2023
DOI: 10.5713/ab.22.0067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation and withdrawal of selenium-enriched kale sprouts on productivity and egg selenium concentration of laying hens

Abstract: The aim of this trial was to investigate the effect of supplementation and withdrawal of selenium-enriched kale sprouts (SeKS) on productivity and egg Se concentration of laying hens. Selenium from commercial Se-enriched yeast (SeY) was used as a comparative Se source.Methods: One-hundred and eighty 61-week-old laying hens were randomly divided into 5 treatment groups with 4 replicates (9 hens each) in a 2x2+1 Augmented Factorial Experiment in a completely randomized design (CRD). The experimental diets were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…The T3 treatment showed numerically higher egg production, although not statistically significant, it probably due to a high standard deviation in this variable. In agreement with this finding, a previous study showed inconsistent egg productivity in response to Se dosage (Chantiratikul et al, 2023).…”
Section: Egg Production and Qualitysupporting
confidence: 90%
See 1 more Smart Citation
“…The T3 treatment showed numerically higher egg production, although not statistically significant, it probably due to a high standard deviation in this variable. In agreement with this finding, a previous study showed inconsistent egg productivity in response to Se dosage (Chantiratikul et al, 2023).…”
Section: Egg Production and Qualitysupporting
confidence: 90%
“…The increase in egg weight and Haugh Unit further suggest that the supplements promoted albumen quality. One contributing factor that improved performance and egg quality in this study was related to increase ntioxidant capacity and reducing oxidative damage, which indirectly boosted health status and laying performance (Chantiratikul et al, 2023). However, the higher dose of these supplements with 0.675 mg selenium yeast and 200 vitamin E (T4) did not affect the productive performance and egg quality, probably due to adverse effects when these supplements were combined (Schrauzer, 2006;Kim and Kil, 2020;Rahbari, 2020).…”
Section: Egg Production and Qualitymentioning
confidence: 79%